Calculations on nonlinear optical properties for large systems The elongation method - Gu, Feng Long.; Aoki, Yuriko; Springborg, Michael; Kirtman, Bernard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
For design purposes one needs to relate the structure of proposed materials to their NLO (nonlinear optical) and other properties, which is a situation where theoretical approaches can be very helpful in providing suggestions for candidate systems that subsequently can be synthesized and studied experimentally. This brief describes the quantum-mechanical treatment of the response to one or more external oscillating electric fields for molecular and macroscopic, crystalline systems. To calculate NLO properties of large systems, a linear scaling generalized elongation method for the efficient and accurate calculation is introduced. The reader should be aware that this treatment is particularly feasible for complicated three-dimensional and/or delocalized systems that are intractable when applied to conventional or other linear scaling methods.
Survey of Nonlinear Optical Materials -- Quantum-Mechanical Treatment of Responses to Electric Fields $1 (BMolecular Systems -- Quantum-Mechanical Treatment of Responses to Electric Fields $1 (BExtended Systems -- The Elongation Method -- Applications of the Elongation Method to NLO Properties -- Future Prospects.s
Keywords: Chemistry; Chemistry, Physical and theoretical; Proteins; Optics; Electrodynamics; Nanotechnology; Chemistry; Theoretical and Computational Chemistry; Optics and Electrodynamics; Nanotechnology; Protein Science; Electronic books